MEMORIES AND PLAY SETTLERS OF SÃO MIGUEL DO IGUAÇU-BRAZIL (Fiep Bulletin - online, 2011)
According to (ALVES, 2004, p. 54), "the culture relates to humanity as a whole and at the same time each of the people. When considering a particular culture that exists or has existed, soon finds his great variation ". This way, it is essential to understand the senses that a cultural reality is for those who live. The problematic that boosted this study was: the playful culture of German and Italian settlers, and what they do in your spare time? Having as main objective, to rescue the playful culture from memory immaterial of German and Italian settlers of São Miguel do Iguaçu, Paraná State. Included in the sample ten settlers of São Miguel do Iguaçu, being two Germans and eight Italians. Data analysis was performed with the search for bibliographic surveys and historiográficos, with content analysis and field research, where were made interviews with settlers. So, tried to rescue the history of migrants residing in São Miguel do Iguaçu-Brazil (SMI), is said in this scenario, to rescue the playful culture from memory and memories of the settlers. To do this, it was necessary to give voice to these subject, so that they could report with vivacity about his childhood. The colonists did not have much time to play, and the time they had was spent at work in the plantation, and when he had some time off, leaving to hunt, go to the home of friends and neighbors. It was noted that were healthy games much integration and socialization, mainly between the neighbouring families or relatives. Certainly being loaded significances, social and cultural rights, the banter and toys allowed some mysteries that still unravel are rooted in their everyday life and culture of these settlers.
Keywords: playful culture; toys and games